Arterial resection during pancreatectomy for pancreatic ductal adenocarcinoma with arterial invasion: A single-center experience with 109 patients. Issue 37 (11th September 2020) - Kwon, Jaewoo; Shin, Sang Hyun; Yoo, Daegwang; Hong, Sarang; Lee, Jong Woo; Youn, Woo Young; Hwang, Kyungyeon; Lee, Seung Jae; Park, Guisuk; Park, Yejong; Lee, Woohyung; Song, Ki Byung; et al.
Abstract : Abstract: Pancreatectomy for pancreatic cancer with arterial invasion is controversial and performed infrequently. As its indication evolves and neoadjuvant chemotherapy also evolves, it is meaningful to identify short- and long-term outcomes of pancreatectomy with arterial resection (AR). This study aimed to retrospectively analyze the clinical outcomes of pancreatectomy with AR for pancreatic ductal adenocarcinoma. Patients with pancreatic ductal adenocarcinoma treated with pancreatectomy with AR at our institute between January 2000 and April 2017 were retrospectively reviewed. Operative outcome and survival were compared according to the presence of neoadjuvant chemotherapy. This study included 109 patients (38 underwent surgery after neoadjuvant chemotherapy, 71 underwent upfront surgery). The median hospital stay was 17 (interquartile range, 12–26.5) days. Clinically relevant postoperative pancreatic fistula (grade B or C) occurred in 14 patients (12.8%). The major morbidity (≥grade III) and mortality rates were 26.6% and 0.9%, respectively. R0 resection was achieved in 80 patients (73.4%). Microscopic actual tumor invasion into the arterial wall was identified in 25 patients (22.9%). The median overall survival (OS) of all patients was 18.4 months. The neoadjuvant chemotherapy group showed better OS than the upfront surgery group, without statistical significance (25.3 vs 16.2 months, P = .06). Progression-free survival was better in patients with neoadjuvant chemotherapy (13.2 vs 7.1 months, P = .01). Patients with partial response to neoadjuvant chemotherapy showed better OS than those with stable disease (33.7 vs 17.5 months, P = .04). Pancreatectomy with AR for advanced pancreatic cancer showed acceptable procedure-related morbidity and mortality. A survival benefit of neoadjuvant chemotherapy was identified, compared to upfront surgery. Abstract : Supplemental Digital Content is available in the text